2011
DOI: 10.1007/s00428-011-1062-5
|View full text |Cite
|
Sign up to set email alerts
|

EGFR/erB-1, HER2/erB-2, CK7, LP34, Ki67 and P53 expression in preneoplastic lesions of bronchial epithelium: an immunohistochemical and genetic study

Abstract: A prognostic interpretation of preneoplastic lesions would have impact in bronchial carcinoma early diagnosis and through the study of Erb-B family receptors as they have an important role in lung carcinogenesis. The existence of drugs as tyrosine kinase inhibitors stressed the importance of studying gene alterations for selected chemoprevention schemes and characterization of carcinogenesis. Bronchial preneoplastic lesions were characterized by immunohistochemistry using the antibodies LP34 (high weigh molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
9
0
1
Order By: Relevance
“…We have studied EGFR expression in these pre-neoplastic lesions, demonstrating its increasing expression in lesions in this spectrum; therefore, EGFR and its respective pathways may play a role in early steps of epidermoid carcinoma development, reflecting the importance of EGFR signalling transduction pathways in pre-neoplastic lesions [1]. Other studies also corroborate these results [2][3][4][5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…We have studied EGFR expression in these pre-neoplastic lesions, demonstrating its increasing expression in lesions in this spectrum; therefore, EGFR and its respective pathways may play a role in early steps of epidermoid carcinoma development, reflecting the importance of EGFR signalling transduction pathways in pre-neoplastic lesions [1]. Other studies also corroborate these results [2][3][4][5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 69%
“…An increasing expression of these markers was observed [1]. The study reinforced the utility of Ki-67 as a biomarker for dysplasia, a group of pre-neoplastic lesions characterized by a higher proliferative index, also identified by other authors [1,[12][13][14][15][16][17].…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Also, Cavarga et al [27] and Hoshino et al [28] indicated that increases in Ki-67 expression in preneoplastic lesions might be associated with the development of bronchogenic carcinomas and possibly with acquisition of an invasive phenotype. Ki-67 appears to correlate with the progression of the malignant processes from the preneoplastic to the invasive stage [29], and may be useful in predicting prognosis in patients with non small-cell lung cancer [30]. However, further studies are needed to explore this concept.…”
Section: Discussionmentioning
confidence: 99%